Appraisal of the Treatment Efficiency with Direct-Acting Anticoagulants in Ophthalmic Practice. Literature Review - M. A. Frolov; U. S. Plyaskina; I. V. Vorobyeva; A. M. Frolov; V. V. Biryukov; S. Shallah (Oftalʹmologiâ, 2023)
Diabetic retinopathy (DR) is a disease that irrevocably leads to blindness, especially in the absence of proper monitoring and treatment. World statistics on its prevalence are not comforting. This pathology has always demanded and will continue to demand high attention from endocrinologists and ophthalmologists. In search of competent patient management, we have studied scientific papers on various treatment approaches with proven positive research results. We decided to analyze the drug Sulodexide, since in many studies it has proven to be a safe and effective direct anticoagulant with minimal side effects. As it turned out, Sulodexide is effective not only in relation to DR, but also in other pathologies of the fundus, which is described in this article.